Immunotherapy yields breed-specific worst survival outcomes among three investigated therapies in French bulldogs with high-grade glioma - Susan A. Arnold; Amanda R. Taylor; Katherine Hansen; Vijay Agarwal; Walter C. Low; G. Elizabeth Pluhar (Frontiers in Veterinary Science)
IntroductionFrench bulldogs are one of the most popular dog breeds in the United States and are also among breeds with the highest risk for developing high-grade glioma (HGG). With limited treatment options and high translational value for studying canine HGG to advance understanding of human glioblastoma (GB), a variety of novel treatment options have been investigated. In other forms of cancer, immunotherapy has shown promising results, garnering interest in the treatment of HGG. Yet, when an immunotherapy-based clinical trial was conducted, a marked survival disparity in French bulldog patients compared to other breeds was observed.MethodsThis retrospective, multi-institutional study was conducted to examine survival outcomes in immunotherapy-treated French bulldogs compared to closely related breeds, and to French bulldogs treated with several other treatment modalities.ResultsFrench bulldogs treated with immunotherapy experienced significantly shorter overall survival (OS) than boxers and Boston terriers (132 vs. 221 days, respectively). French bulldogs treated with immunotherapy had no significant difference in OS compared to French bulldogs treated palliatively, whereas dogs treated with either a novel therapy involving sonodynamic therapy or stereotactic radiation therapy had significantly longer OS.DiscussionThis study provides evidence for an immunotherapy-resistant form of HGG in French bulldogs, suggesting that the breed harbors key molecular differences affecting the tumor and tumor-immune microenvironment and subsequent poor response to treatment.